Synthesize monolayer graphene on SiO2/Si substrate with copper-vapor-assisted CVD method. (21st September 2018) - Zhang, Wenqing; Zhang, Lianchang; Zhang, Hui; Song, Lingling; Ye, Qianxu; Cai, Jinming
Abstract: The growth of high quality graphene on an insulator substrate such as SiO2 /Si broadens the way for the development of graphene-based electronic devices, which still remains significant attraction. Here, we present an approach to directly synthesize high quality single layer graphene (SLG) on SiO2 substrate with Cu-vapor-assisted chemical vapor deposition (CVD). Because Cu is in vapor state, not only it catalyzes the pyrolysis of hydrocarbon precursors and accelerates the nucleation, but also it won't remain on the graphene surface nor under the graphene. Different testing methods confirm that large scale, high quality of SLG is successfully synthesized. Furthermore, the graphene has good conductivity and transparency. Therefore, this method bares great potential in future electronic applications.